Справочник по технологии лазерной обработки - Коваленко В. С. Владимир Сергеевич; Котляров В. П. Валерий Павлович; Дятел В. П. Владимир Петрович; Головко Л. Ф. Леонид Федорович (Киев, Технiка, 1985)
Авт. указаны на обороте тит. л.